A study of clinico epidemiological profile and relevance of patch testing in patients with hand eczema - Babu, Kotapati Narendar; Manickam, Navakumar; Gopalan, Kannan (Journal of Pakistan Association of Dermatologists, 2022)
Introduction: Hand eczema (HE) is a common occupational disease caused by diverse etiological factors and severity ranges from mild to severe withÂ prolonged clinical course creating a negative impact on the quality of life. Therefore, for proper management of HE, identification and avoidance of triggering contact allergens is important. Aim : To study the various morphological patterns and to identify the exogenous allergens causing hand eczema(HE) with the use of Indian standard series of patch test. Materials and Methods: This was a cross-sectional prospective study and a total of 60 patients with hand eczema aged 18years and above were included. Patch tests were applied to upper back and readings were recorded after 48hrs. Data were coded and analysed at the end of study. Results: Of the 60 patients, 37(64%) were females and 23(36%) were males. About 28 (46.7%) of them were between age group of 41 to 60years. House wives 14(23.3%) were most commonly affected followed by farmers 13(21.7%). The common morphological pattern seen was chronic scaly eczema in 18 patients (30%) followed by nummular eczema in 11 patients (18.3%). Atopic history was positive in 16(26.6%) patients. Patch test was positive in 13(22%) patients and most common allergen found was potassium dichromate. Conclusion: This study depicts various morphological patterns of hand eczema and the exogenous allergens causing them. Identifying and avoiding the exogenous allergens is important as it helps the patients free from disease andÂ also Â improves the quality of life.